Assessing the Socio-Economic Impacts of the PLBN Entikong National Strategic Project in Entikong District, Sanggau Regency - Azharisman Rozie; Tri Yuni Rahmawati; Selvi Diana Meilinda (Khazanah Sosial, 2025)
This research examines the socio-economic impacts of the PLBN Entikong national strategic project on the community in Entikong District, Sanggau Regency. mploying a quantitative approach, the research utilizes Partial Least Squares Structural Equation Modeling (PLS-SEM) via SmartPLS software to analyze the relationships between infrastructure development and community welfare indicators. Data were collected through purposive sampling, involving 50 respondents selected for their direct engagement with the project, and triangulated through structured questionnaires and field observations. The analysis confirms statistically significant positive impacts of the PLBN Entikong project on both social and economic dimensions, as evidenced by T-statistic values exceeding 1.96 (p < 0.01). Social improvements include enhanced community collaboration and cultural integration, while economic benefits manifest in increased local trade activity and income growth. However, disparities in policy implementation—such as limited local vendor participation (68% exclusion) and underutilized human resource budgets (22% absorption)—highlight systemic gaps requiring redress. These findings underscore the project’s role as a catalyst for inclusive development while emphasizing the need for participatory governance and adaptive policy frameworks. The study contributes actionable insights for optimizing border development strategies and advancing equitable socio-economic outcomes in Indonesia’s marginalized frontier regions.